Genetic and Biochemical Characterization of Field-Evolved Resistance to Bacillus thuringiensis Toxin Cry1Ac in the Diamondback Moth, Plutella xylostella - Sayyed, Ali H. (American Society for Microbiology, 2004)
The long-term usefulness of Bacillus thuringiensis Cry toxins, either in sprays or in transgenic crops, may be compromised by the evolution of resistance in target insects. Managing the evolution of resistance to B. thuringiensis toxins requires extensive knowledge about the mechanisms, genetics, and ecology of resistance genes. To date, laboratory-selected populations have provided information on the diverse genetics and mechanisms of resistance to B. thuringiensis, highly resistant field populations being rare. However, the selection pressures on field and laboratory populations are very different and may produce resistance genes with distinct characteristics. In order to better understand the genetics, biochemical mechanisms, and ecology of field-evolved resistance, a diamondback moth (Plutella xylostella) field population (Karak) which had been exposed to intensive spraying with B. thuringiensis subsp. kurstaki was collected from Malaysia. We detected a very high level of resistance to Cry1Ac; high levels of resistance to B. thuringiensis subsp. kurstaki Cry1Aa, Cry1Ab, and Cry1Fa; and a moderate level of resistance to Cry1Ca. The toxicity of Cry1Ja to the Karak population was not significantly different from that to a standard laboratory population (LAB-UK). Notable features of the Karak population were that field-selected resistance to B. thuringiensis subsp. kurstaki did not decline at all in unselected populations over 11 generations in laboratory microcosm experiments and that resistance to Cry1Ac declined only threefold over the same period. This finding may be due to a lack of fitness costs expressed by resistance strains, since such costs can be environmentally dependent and may not occur under ordinary laboratory culture conditions. Alternatively, resistance in the Karak population may have been near fixation, leading to a very slow increase in heterozygosity. Reciprocal genetic crosses between Karak and LAB-UK populations indicated that resistance was autosomal and recessive. At the highest dose of Cry1Ac tested, resistance was completely recessive, while at the lowest dose, it was incompletely dominant. A direct test of monogenic inheritance based on a backcross of F(1) progeny with the Karak population suggested that resistance to Cry1Ac was controlled by a single locus. Binding studies with (125)I-labeled Cry1Ab and Cry1Ac revealed greatly reduced binding to brush border membrane vesicles prepared from this field population.